1991
DOI: 10.1021/ma00021a002
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the preparation of a block copolymer from macroradicals produced in viscous media

Abstract: Extensive experiments on copolymer syntheses as a type of dispersion polymerization in viscous poor solvents (e.g., silicone oil) have been reported (Seymour, R. B.; Kincaid, P. D.; Owen, D. R. Adv. Chem. Ser. 1973,129,230) which, based on a trapped-macroradical model, were taken to suggest that such conditions promoted the formation of block copolymers. Here we report the results of a series of tests devised to elucidate the mechanisms in these systems. One such test used initiation by y radiolysis of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…These heterogeneous radical polymerizations entrapped propagating species in insoluble polymer particles and extended their lifetime. However, Louis et al 16 reported that the entrapped macroradical model in a viscous solvent is doubtful in the dispersion polymerization of St and demonstrated that graft and statistical copolymers are formed in the process. Zhang et al 15 also did not rule out the possibility of graft copolymer formation occurring in the consecutive copolymerization in ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These heterogeneous radical polymerizations entrapped propagating species in insoluble polymer particles and extended their lifetime. However, Louis et al 16 reported that the entrapped macroradical model in a viscous solvent is doubtful in the dispersion polymerization of St and demonstrated that graft and statistical copolymers are formed in the process. Zhang et al 15 also did not rule out the possibility of graft copolymer formation occurring in the consecutive copolymerization in ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…The crude copolymer sample 2-2c (56.70 mg) was extracted to remove each homopolymer at 80 °C for 24 h using selective solvents, i.e., cyclohexane for PSt and acetonitrile for PM-MA. 15,16,33,34 After the selective extraction, the residue was dissolved in CHCl3 at room temperature. The fractions (7.9, 10.9, and 80.9 wt %) were characterized with 1 H NMR (see Supporting Information), FTIR, and GPC (Table 3).…”
Section: Introductionmentioning
confidence: 99%
“…acetonitrile for PMMA and cyclohexane for PSt, respectively. [39][40][41][42] After the selective extraction, the residual part was dissolved in CHCl 3 at room temperature. Each fraction was characterized with 1 H NMR, FT-IR and GPC.…”
Section: Copolymerizationmentioning
confidence: 99%
“…To determine the copolymer structure, the selective solvent fractionation method [39][40][41][42] was applied to the consecutive copolymerization sample 2-1c. The as-polymerized sample 2-1c was extracted to remove each homopolymer at 80 8C for 24 h using the selective solvents cyclohexane and acetonitrile for PSt and PMMA, respectively.…”
Section: Copolymerizationmentioning
confidence: 99%
“…These heterogeneous radical polymerizations entrapped the propagating species in insoluble polymer particles and extended their lifetime. However, Louis et al19 reported that the entrapped macroradical in a viscous solvent is a doubtful model, especially in the dispersion polymerization of St. They did this by demonstrating that graft and statistical copolymers were formed in the process.…”
Section: Introductionmentioning
confidence: 99%